2016
DOI: 10.4047/jap.2016.8.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abutment screw length and cyclic loading on removal torque in external and internal hex implants

Abstract: PURPOSEThe purpose of this study was to evaluate the effects of abutment screw length and cyclic loading on the removal torque (RTV) in external hex (EH) and internal hex (IH) implants.MATERIALS AND METHODSForty screw-retained single crowns were connected to external and internal hex implants. The prepared titanium abutment screws were classified into 8 groups based on the number of threads (n = 5 per group): EH 12.5, 6.5, 3.5, 2.5 and IH 6.5, 5, 3.5, 2.5 threads. The abutment screws were tightened with 20 Ncm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 23 publications
2
23
0
1
Order By: Relevance
“…These results are similar to those of several studies. Mohammed et al [17] reported that the post-loading RTVs of internal hex implants were significantly lower than the initial RTVs after 16,000 cycles and Cibirka et al [26] found decreasing RTVs in the internal hexagon of Nobel Biocare implants after 5 million cycles of fatigue testing. The decrease in RTVs after cyclic loading can be explained by the micromovement of the joint connection or progressive settling effect from functional loading [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are similar to those of several studies. Mohammed et al [17] reported that the post-loading RTVs of internal hex implants were significantly lower than the initial RTVs after 16,000 cycles and Cibirka et al [26] found decreasing RTVs in the internal hexagon of Nobel Biocare implants after 5 million cycles of fatigue testing. The decrease in RTVs after cyclic loading can be explained by the micromovement of the joint connection or progressive settling effect from functional loading [33].…”
Section: Discussionmentioning
confidence: 99%
“…It causes the two surfaces to come closer together and leads to axial displacement. This axial displacement causes the length of the abutment screw to shorten, diminishing the screw preload [17]. The settling effect is the main cause of screw loosening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in the RTV compared to the tightening torque is a result of embedment relaxation [24]. When abutment screw is subjected to torque application, micromovements between the screw and the internal surface of implant occur and the irregularities on the screw surface are flattened [25]. Such a wear between the surfaces in contact with each other approximates the metal surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, a manifestação das cargas biomecânicas nos implantes dentais (momentos, tensão e pressão) controla a saúde da interface osso-implante a longo prazo (MISCH, 2015). (ARAT BILHAN et al, 2015;AYLLÓN et al, 2014a;BICUDO et al, 2016;CHEN et al, 2015;GHADIRI et al, 2015;HERNANDEZ-RODRIGUEZ et al, 2015;JAMSHIDINIA et al, 2015;KAYABAŞI et al, 2006;LIN et al, 2009;MACEDO et al, 2017;MINATEL et al, 2017;MOHAMMED et al, 2016;PRADOS-PRIVADO et al, 2017;SANTIAGO et al, 2016b;TOPKAYA;SOLMAZ, 2015;WOLFF et al, 2014 BILHAN et al, 2015;BORDIN et al, 2015;CHUN et al, 2002;DJEBBAR et al, 2010;HERNANDEZ-RODRIGUEZ et al, 2015;ILIES et al, 2008;KAYABAŞI et al, 2006;KOHN, 1991;MACEDO et al, 2017;MINATEL et al, 2017;PAN et al, 2015;PRADOS-PRIVADO et al, 2015;ŞAHIN;ÇEHRELI;YALÇIN, 2002;SANIVARAPU et al, 2016;SHEMTOV-YONA et al, 2014a, 2014cSKALAK, 1983 De acordo com Dieter (1981), os fatores básicos necessários para causar falha devido fadiga são:…”
Section: Introductionunclassified